Green synthesis of Hesperitin dihydrochalcone glucoside by immobilized α-l-rhamnosidase biocatalysis based on Fe3O4/MIL-101(Cr) metal-organic framework. (1st July 2022) - Wang, Chunqing; Xia, Na; Zhu, Siming; Chen, Lin; Chen, Liang; Wang, Zhendong
Graphical abstract: In this paper, a green and efficient method of immobilizing α-l -rhamnosidase to synthesize HMGDC was proposed. Based on MIL-101(Cr) precursor, magnetic MOF Fe3 O4 /MIL-101(Cr) was successfully synthesized. The immobilized α-l -rhamnosidase reaction platform was established, and the feasibility of the bioenzymatic synthesis of high-value sweetener HMGDC was verified by using HSDDC with better water solubility as substrate. Firstly, the morphology and structure of Fe3 O4 / MIL-101(Cr) magnetic materials were characterized. Secondly, the enzymatic properties of free and immobilized enzyme were analyzed. Finally, the product HMGDC was isolated and purified, and verified by TOF-MS. The immobilized enzyme showed excellent activity and thermal stability, which effectively improved the substrate conversion rate, reuse rate and reduced the cost of industrialization. To our knowledge, this is the first time that α-l -rhamnosidase was immobilized by magnetic MOF material to prepare HMGDC. Highlights: Free enzymes were successfully immobilized on Fe3 O4 /MIL101(Cr) magnetic nanomaterials. The activity of immobilized enzyme reached 293.55 U/g, which was higher than that of free enzyme. After 9 cycles, the activity of the immobilized enzyme about 30%. The conversion rate of HSDDC into HMGDC reached 93.1% using the immobilized enzyme for the first time. Abstract: In this study, α-l -rhamnosidase was immobilized on magnetic Fe3 O4 /MIL-101 (Cr) nanoparticles using MIL-101(Cr) as precursor by crosslinking method. The crosslinking agent concentration ratio and crosslinking time were EDC/NHS 1:1 and 2 h, respectively. The immobilized materials were characterized by FT-IR, XRD, SEM and VSM. The saturation magnetization of the prepared magnetic nanoparticles was 46.2 emu/g. The optimum pH and temperature of immobilized enzyme were 6 and 60 °C. The application of immobilized enzyme in the preparation of hesperidin dihydrochalcone glucoside (HMGDC) by hydrolysis of hesperidin dihydrochalcone (HSDDC) was studied. The results showed that immobilized enzyme had better temperature resistance, repeatability and stability than free enzyme. The immobilized enzyme activity was 293.55 U/g, and the recovery was 116.03%. After treatment at 60 °C for 4 days, the enzyme activity remained at 24.6%. The conversion rate of HSDDC reached 93.1%.